ASSESSMENT OF FRACTIONAL COMPOSITION OF THE INDUSTRIAL DUST COMING TO THE ATMOSPHERE OF THE CITY (ON THE EXAMPLE OF THE DUST WHICH IS ALLOCATED FROM THE ELECTROSTEEL-SMELTING FURNACE) - Elena Anatolievna Semyonova; Natalia Mihailovna Sergina; Denis Valer'ievich Azarov; Ivan Aleksandrovich Gvozdkov (Современная наука и инновации)
At the Volgograd state architectural and construction university (VolgGASU) for many years researches of fractional structure and properties of the dust arriving on urban air environment from sources of various productions are conducted. Results of such assessment for the dust which is allocated in the atmosphere of the city when melting steel in arc electric furnaces are given in the present article.